Epidemiology and etiology of ganoderma upper and basal stem rot in oil palm (elaeis guineensis jacq.) on peat in Sarawak, Malaysia - Mohd Rashid, Mohd Rakib (2015)
Oil palm (Elaeis guineensis) is the world’s most important oil producing crop which is mostly cultivated in Southeast Asia. The sustainability of oil palm is threatened by Ganoderma species that cause upper stem rot (USR) and basal stem rot (BSR). Basal stem rot is a prominent disease of oil palm, while little is known about USR. Lack of knowledge in terms of epidemiology and etiology of the diseases may lead to inaccurate disease control strategies. A study was conducted in oil palm plantations on peat in Sarawak, Malaysia, namely, Sessang Estate in Betong and Sungai Balim Estate in Miri. A total of 46 isolates of Ganoderma species from the USR- and BSR-infected palms were identified using multiplex PCR, and their in-vitro cultural and basidiospore morphological characteristics were investigated. It was found that both USR and BSR were associated with similar pathogens, where G. zonatum (71.7%) was dominant, followed by G. boninense (26.1%) and G. miniatocinctum (2.2%). This suggests that G. zonatum may have played a more vital role in the epidemiology of the disease than previously believed. All samples were found incompatible based on somatic compatibility test which indicated genetic heterogeneity of Ganoderma species in oil palm plantation and was suggestive of disease spread via spore dispersal that generated new genetically distinct individuals. There were also significant variations within and between Ganoderma species and no distinct relationship were found between species, disease types or geographical origins in terms of their cultural morphology and basidiospore characteristics. This suggests that any of the Ganoderma isolates found in this study have similar possibility of either causing USR or BSR. The pathogenic capability and aggressiveness of Ganoderma species were assessed based on external and internal infection symptoms using artificial inoculation on oil palm seedlings throughout 24 weeks period. All 46 Ganoderma samples tested were confirmed to be pathogenic to oil palm. Among them, G. zonatum isolated from USR-infected palms showed superior aggressiveness as compared with others with average foliar symptoms severity (FSS), disease severity index (DSI), stem bole lesion and primary root decay up to 33.18%, 43.78%, 42.20% and 48.55%, respectively. Hence, besides the prominent G. boninense and BSR, more studies should emphasize on G. zonatum and USR for more effective disease management since it was found as an increasingly important pathogen and disease in oil palm plantations, especially on peat areas in Sarawak. The infection of USR and BSR were mainly confirmed based on appearance of Ganoderma basidiomata on the stem, while the point of infection on the stem was the distinctive characteristic between them, where infection of Ganoderma species about one meter above ground indicated USR, while that at the base indicating BSR. USR and BSR disease coexisted in both sites, with lower USR (1.14-1.32%) as compared with BSR (3.48-4.01%) in Betong, while higher USR (3.66-6.02%) as compared with BSR (0.87-3.78%) in Miri throughout the study period. This also indicated that Ganoderma species infection in Miri was relatively higher than that in Betong. Geostatistical analysis of the Ganoderma species distribution revealed generally weak spatial dependence (>75%), which indicated that the distribution was random, and related to Ganoderma species spread via basidiospore dispersal at greater distance, instead of root-to-root infection. It was revealed that spatial distribution of Ganoderma species was at relatively greater density in Miri (15.1-100%) as compared with Betong (15.1- 30%). Although the distribution of Ganoderma species were random, the hotspot patterns generated allow site specific disease management as in precision agriculture and aid in sampling programmes for further investigations on the factors attributed to the patterns. Studies on macro- and micronutrients composition in relation to spatial distribution of Ganoderma species revealed that the foliar macro- and micronutrient elements affected the infection of Ganoderma species. Based on the four trials conducted at the two study sites, it was found that higher level of phosphorus (P), and lower and deficient level of copper (Cu) and zinc (Zn) in oil palms were associated with higher Ganoderma infection. In addition, lower and deficient level of Cu and Zn also could be related to higher Ganoderma infection in Miri as compared with Betong. Furthermore, there was no distinct factor in terms of soil and foliar chemical properties between USR and BSR. Therefore, this finding could be used as general guide to control Ganoderma species by giving more concern on manipulation of P, Cu and Zn level in oil palm plantations generally, and specifically in the two sites in this study for site-specific disease management as in precision agriculture.